Plan of attack - Woodward, Bob, 1943- (Simon & Schuster, 2004)
Bob Woodward's book on President Bush and the Iraq war will be the definitive account of the turning point in history as Bush, his war council and allies launched a pre-emptive attack, toppling Saddam Hussein and taking over the country. From in-depth interviews with key players and notes from national security meetings, Woodward provides a thoroughly original, authoritative narrative of the behind-the-scenes manoeuvring, examining the causes and consequences of the most controversial war since Vietnam.